Age of pandemics, 1817-1920 : how they shaped India and the world - Tumbe, Chinmay (Noida HarperCollins Publishers, 2020)
From lockdowns to lock-ups, viruses to vaccination, the movement of people to the movement of bowels, from rats to cats, and more, The Age of Pandemics chronicles the many facets of the cholera, plague and influenza pandemics, which claimed over 70 million lives between 1817 and 1920, with India being the epicentre in all these episodes. A time otherwise known for the worldwide spread of the industrial revolution, imperialism and globalization, the period between the early nineteenth century and the early twentieth century was also the age of pandemics. This book documents the scale of devastation, the likely causes and consequences, and the resilience with which people faced those uncertain times. It also provides the first comprehensive coverage of the worlds greatest demographic disaster ever to descend upon a country in a short period of time - the influenza pandemic in India in 1918 - which claimed more lives than all the battle casualties of World War I. And it shows the continuing relevance of learning from those times to tackle contemporary challenges, such as COVID-19.
Keywords: Communicable diseases; Epidemics